Implementing sustainable purchasing and supply management (SPSM): A Delphi study on competences needed by purchasing and supply management (PSM) professionals. Issue 4 (October 2020) - Schulze, Heike; Bals, Lydia
Abstract: This research is about a Delphi study that was conducted in the context of the development of a competence model for sustainable purchasing and supply management (SPSM). Based on the findings of a systematic literature review (SLR), it addresses the research gap in this area with the aim to foster the integration of sustainability in purchasing and supply management (PSM) in higher education and in professional training approaches for PSM professionals. The qualitative study was conducted with 16 Delphi experts in the field of PSM and sustainability, applying the critical incident technique (CIT). Together with the findings of the SLR, it led to a specific set of SPSM competences. The theoretical background is based on PSM research, educational sciences and organizational psychology. Highlights: Specific sustainable purchasing and supply management (SPSM) competences are needed to implement sustainability. A Delphi study with 16 experts was conducted, applying the critical incident technique (CIT). The findings confirm competences in the clusters 'cognition-oriented', 'social-oriented', 'functional-oriented' and 'meta-oriented'. Definitions for each competence were derived out of behavioral descriptions gathered with the CIT. The resulting set of SPSM competences provides input for SPSM trainings in the professional and educational context.